Pengembangan Media Lift The Flap Book Berbasis Model Direct Instruction Untuk Meningkatkan Keterampilan Menulis Kalimat Langsung dan Tidak Langsung Siswa - Karimah, Atha Nur; Atha Nur; Sismulyasih Sb, Nugraheti (Universitas Muhammadiyah Magelang, 2026)
This study was motivated by the poor writing skills of fifth-grade elementary school students, especially in direct and indirect sentences. The purpose of this study was to develop a